Abemaciclib in patients with p16ink4A-deficient mesothelioma (MiST2): a single-arm, open-label, phase 2 trial. Issue 3 (March 2022) - Fennell, Dean A; King, Amy; Mohammed, Seid; Greystoke, Alastair; Anthony, Sarah; Poile, Charlotte; Nusrat, Nada; Scotland, Molly; Bhundia, Vina; Branson, Amy; Brookes, Cassandra; Darlison, Liz; et al.
Summary: Background: Genetically stratified therapy for malignant mesothelioma is unavailable. Mesotheliomas frequently harbour loss of the chromosome 9p21.3 locus ( CDKN2A–MTAP ), which is associated with shorter overall survival due to loss of the tumour suppressor p16ink4A, an endogenous suppressor of cyclin-dependent kinase (CDK)4 and CDK6. Genetic restoration of p16ink4A suppresses mesothelioma in preclinical models, underpinning the rationale for targeting CDK4 and CDK6 in p16ink4A-negative mesothelioma. We developed a multicentre, stratified, phase 2 trial to test this hypothesis. Methods: The MiST2 study was a single-arm, open-label, phase 2 clinical trial done two UK centres. Patients older than 18 years with any histologically confirmed subtype of mesothelioma (pleural or peritoneal) with radiological progression after at least one course of platinum-based chemotherapy were molecularly screened by immunohistochemistry for p16ink4A. Patients with p16ink4A-negative mesothelioma were eligible for inclusion in the study. Patients were required to have measurable disease by modified Response Evaluation Criteria in Solid Tumours version 1.1 for malignant mesothelioma, a predicted life expectancy of at least 12 weeks, and an Eastern Cooperative Oncology Group performance status score of 0–1. Patients received oral abemaciclib 200 mg twice daily, administered in 28-day cycles for 24 weeks. The primary endpoint was the disease control rate (patients with complete responses, partial responses, or stable disease) at 12 weeks. The null hypothesis could be rejected if at least 11 patients had disease control. The efficacy and safety populations were defined as all patients who received at least one dose of the study drug. The study is registered with ClinicalTrials.gov, NCT03654833, and is ongoing (but MiST2 is now closed). Findings: Between Sept 31, 2019, and March 2, 2020, 27 eligible patients consented to molecular screening. The median follow-up was 18·4 weeks (IQR 6·7–23·9). One patient was excluded before treatment because of a serious adverse event before study drug allocation. 26 (100%) of 26 treated patients were p16ink4A deficient and received at least one dose of abemaciclib. Disease control at 12 weeks was reported in 14 (54%) of 26 patients (95% CI 36–71). Grade 3 or worse treatment-related adverse events (of any cause) occurred in eight (27%) of 26 patients (diarrhoea, dyspnoea, thrombocytopenia, vomiting, urinary tract infection, increased alanine aminotransferase, ascites, chest infection or suspected chest infection, neutropenic sepsis, alopecia, blood clot left calf, fall [broken neck and collar bone], haemoptysis, lower respiratory tract infection, and pulmonary embolism). Grade 3 or worse treatment-related adverse events occurred in three (12%) of 26 patients (diarrhoea, thrombocytopenia, vomiting, increased alanine aminotransferase, and pulmonary embolism). Serious adverse events occurred in six (23%) of 26 patients, leading to treatment discontinuation in one (4%) patient (diarrhoea, urinary tract infection, chest infection, neutropenic sepsis, fall [broken neck and collar bone], haemoptysis, lower respiratory tract infection, and pulmonary embolism). One patient had a serious adverse event related to abemaciclib (diarrhoea). One (4%) of 26 patients died from an adverse event (neutropenic sepsis). Interpretation: This study met its primary endpoint, showing promising clinical activity of abemaciclib in patients with p16ink4A-negative mesothelioma who were previously treated with chemotherapy, and warrants its further investigation in a randomised study as a targeted stratified therapy. Funding: University of Leicester, Asthma UK and British Lung Foundation Partnership, and the Victor Dahdaleh Foundation.